Relevansi Ontologi Brahman dan Ātman dalam Kitab Īṣāvasya Upaniṣad dengan Pluralitas Agama di Indonesia - Puspo Renan Joyo; Siti Murtiningsih (Balai Penelitian dan Pengembangan Agama Semarang, 2021)
Indonesia is a plurality country which is indicated by the diversity of ethnicities, races, customs, languages, and religions. Plurality, including religion, can have implications for cooperation but also conflict. The facts show that the plurality of religions in Indonesia is in trouble. But inherently, all religions, including Hinduism, also have values that can overcome the problem of plurality, which is hidden in its theological concepts. This study aims to explore the Brahman and Ātman in the Īṣāvasya Upaniṣad ontologically and its relevance to the plurality of religions in Indonesia. This research is library research using a qualitative approach. The material objects of the research are Brahman and Ātman in the Īśāvasya Upaniṣad. Data collection in this study was carried out through document studies on primary and secondary data sources. Data analysis in this study used methodical steps of descriptive, interpretative, and holistic analysis. The results showed that the study of Brahman and Atman was ontologically described in several categories, including substance, quantity, quality, place, time, position, ownership, and action. In addition, this study contains value concepts relevant to religious plurality, including kinship, tolerance, harmony, divinity, holiness, nobility, brotherhood, empathy, love, and mutual respect.